Happiness surveys: exclusive guides for policy? - Gunther Tichy (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2014)
Happiness is increasingly named as a target of policy measures. Apart from the confusing fact that the attention-grabbing catchword 'happiness' refers to 'life satisfaction' in most cases, this approach appears preferable to alternatives as utility functions, magic polygons or to the opaque decisions of politicians. A life-satisfaction-oriented policy would prove welfare-improving, focusing on fair distribution of income and wealth, social goals and institutional goals such as health, freedom and social capital. However, these advantages would come at a price: medium-term life satisfaction goals would clash with longer-term aspects resulting from behaviour which is not aimed at sustainability, yet has a direct impact on it. The second problem is that the respondents can misjudge the satisfaction resulting from their choices, and may not be aware of the (longer-term) consequences of their decisions. Furthermore, policy cannot control some of the central elements of life satisfaction, which means that citizens will sooner or later discover that policy cannot live up to its promise. 'Happiness' as a policy goal cannot relieve politicians from constantly assessing trade-offs and sustainability and searching for compromises among the conflicting ideological positions.
Keywords: D12; D63; D7; E61; 330; happiness; life satisfaction; sustainable policy